Treatment of Metabolic Syndrome in Children - Fornari, Elena; Maffeis, Claudio (Frontiers in Endocrinology, 2019)
The Metabolic Syndrome may be tentatively defined as the clustering of several metabolic risk factors in the same individual. A progressively higher number of children and adolescents is affected by this syndrome worldwide, mainly as a consequence of the constant increase of the prevalence of obesity and sedentary habits. As obesity, the chance that the metabolic syndrome traks into adulthood is high. Moreover, the evidence of an association between the duration of the exposition to metabolic risk factors and morbidity and mortality justifies early treatment and prevention of the metabolic syndrome in both children and adolescents. Treatment includes behavioral interventions, adequate nutrition and physical activity, and, if necessary, pharmacological treatments aimed at reducing excessive weight, dyslipidemia, hypertension and glucose impairments. A multidisciplinary and staged approach to treatment, which includes pediatrician, mental health practitioner, dietician and nurses, is crucial. Usually, the reduction of fat mass promotes an overall improvement of all the components of the metabolic syndrome. Nevertheless, every single component of the metabolic syndrome should be treated as quickly as possible, by using the best current practice. Drugs may be necessary for treating hypertension, type 2 diabetes mellitus and dyslipidemia. In selected cases of gross obesity resistant to treatment, surgical therapy may be also performed.